Система управління якістю електротехнічної продукції та шляхи її удосконалення - Лободзинська, Т. П. (Видавництво Львівської політехніки, 2014)
Розглянуто систему управління якістю електротехнічної продукції на підприємствах та шляхи і напрями її удосконалення з метою забезпечення і підвищення конкурентоспроможності продукції, що випускається. З метою наукового та практичного обґрунтування програми із запровадження системи управління якістю електротехнічної продукції здійснено огляд та узагальнення положень законодавчої бази, стандартів, технічних умов та інших нормативних документів. Запропоновано групування джерел інформації за класифікаційними ознаками для цілей економічного аналізу, що відповідає цілям і завданням проведення аналізу витрат на якість. Комплексна система управління якістю електротехнічної продукції підприємства охоплює достатньо широке коло завдань: систематизацію цілей і завдань управління якістю, визначення функціональних зв’язків, розроблення регламентувальних, стимулювальних і регулювальних дій стосовно процесу забезпечення якості продукції. Запропоновано згрупувати і зафіксувати вищезазначені завдання у Положенні підприємства «Планування, облік та аналіз витрат на якість електротехнічної продукції», що містить сукупність уніфікованих процесів, які встановлюють послідовність процедур планування, обліку та аналізу витрат на забезпечення якості електротехнічної продукції. У межах процесу пропонується стандартизувати чотири процеси: процес планування, процес обліку, процес аналізу та процес оцінювання витрат на якість. The electrical products quality management system on enterprises is examined, as well as the ways and directions of its modernization for the purpose of improvement and provision of the competitiveness of turned out products. The quality of products acts as a basis of enterprise competitiveness. The properly chosen strategy of products quality management will ensure effective development of enterprise and improve the competitiveness of turned out products. The lack of effectiveness of quality management systems that were used in our country, has necessitated the search for and study of new forms, methods and means of improving and ensuring products quality. For the purpose of scientific and practical grounding of the program of electrical products quality management system introduction the provisions of the legal framework, standards, specifications and other regulations were reviewed and summarized. Informational base of electrical products quality cost analysis is formed in accordance with the goals and objectives of the analysis, combining internal and external data sources. The process of database formation begins with an assessment of different sources from which the information is received, and is rested on such criteria as reliability, accuracy, timeliness, usefulness, etc. A grouping of sources of information by classification characteristics for the purposes of economic analysis is proposed, that reflects the aims and objectives of the analysis of quality cost. Comprehensive electrical products quality management system on enterprise covers quite a wide range of tasks: the systematization of the goals and objectives of quality management, the definition of functional relationships, development of regulatory, incentive and regulatory actions for the process of ensuring products quality. The paper proposes to group and fix the abovementioned tasks in the Enterprise Regulation «Planning, accounting and cost analysis of electrical products quality». It contains a set of standardized processes that establish the sequence of procedures for planning, accounting and analysis of cost of electrical products quality. In the framework of the process it is proposed to standardize the four processes: planning, accounting, analysis and evaluation of quality cost. The compliance with the requirements set out in the Regulation, provides an opportunity for the manufacturer to assess the conformity of the products quality with the market needs, such as: provides the receipt of reliable information about the quality cost and the required level of quality of turned out products, while minimizing the total cost of its production, helps to determine the size of needed investment in the interests of improving the quality of products and processes, to manage the technical and economic level of products according to the international standards and to determine the effectiveness of the quality management system functioning as a whole. The application of the given Regulation and the implementation of the proposed approaches to electrical products quality evaluation and cost analysis will generate the information necessary for making effective management decisions on products quality. Quality cost analysis will reveal the reserves of increasing enterprise efficiency and, consequently, increasing its competitiveness in the market.
The electrical products quality management system and the ways of its modernization
Keywords: система управління якістю; електротехнічна продукція; конкуренто-спроможність продукції, що випускається; Положення підприємства «Планування, облік та аналіз витрат на якість електротехнічної продукції»; процес планування; процес обліку; процес аналізу та процес оцінки витрат на якість; quality management system; electrical products; competitiveness of turned out products; Enterprise Regulation «Planning, accounting and cost analysis of electrical products quality»; planning process accounting process; analysis process and evaluation of quality costs process